(untitled) (Applied Biological Research, 2018)
The study was conducted to assess the toxic effect of topical use of different synthetic acaricides on yellow mite (Polyphagotarsonemus latus) and its predatory mite (Amblyseius ovalis). Both the mites were collected and cultured separately on chilli plants grown in cups of 6 cm dia. during early winter of 2014 and 2015, under ventilated glass-house conditions. Acaricide application under laboratory conditions showed that fenpyroximate 5 EC @ 1 mL L-1 and propargite 57 EC @ 2 mL L-1 were most toxic and caused highest mortality of P. latus i.e. 98.2 and 96.8% with LC50 values of 12.09 and 21.95 ppm, respectively. The least mite reduction was shown by sulphur 80 WP (81.55%) with LC50 value of 210.3 ppm. Comparing the acaricides applied, fenpyroxi-mate 5 EC and propargite 57 EC were less toxic to predatory mites inflicting 49.1 and 54.1% mortality with respective LC50 values of 96.1 and 164.2 ppm.